Effects of Strategic Management Drivers on Performance of Airports in Kenya - Koros, Rosemary Chebet; Namusonge, Prof. G. S.; Sakwa, Prof. M.M. (IJRDO - Journal of Business Management, 2018)
The main objective of this study is to establish the effect of strategic management drivers on performance of airports in Kenya. This study is guided by the following specific objectives:- to find out the effects of strategic human capital on performance of airports in Kenya, to establish the effects of safety and security strategy on airports performance in Kenya, to determine the effects of strategic customer focus management practices on airports performance in Kenya, and to establish the effects of use of strategic ICT on airports performance in Kenya . The study is based on the Contingency theory and Stakeholder theory. The study will adopt correlational research design and will use both statistics (quantitative) and themes (qualitative) to develop strong evidence in support of the study variables.The target population of the study comprises of 2078 respondents cutting across the whole organization ranging from senior managers to staff that are directly linked to the airports operations from all the airports in Kenya.